Os planos industriais brasileiros de 2004 e 2008 e seus efeitos sobre o setor industrial: um enfoque evolucionista - Macorin, Guilherme (2013)
The current work presents the evolutionist premises of the growing of the firm in order to evaluate the theoretical bases of the PDP and PITCE industrialization plans, both of them implemented by the Brazilian Government in 2004 and 2008, respectively. It will also be presented the assumptions of the plans and the measures put in practice, allowing an analysis comparing what had been proposed and what have been accomplished. Finally, it is also presented a study with the economical results of the industrial sectors involved on the plans, to verify whether the established goals were achieved. With such instruments it will be possible to make conclusions about the effectiveness of the current actions of the Federal Government